"Shorts last sunday, snow pants today": Delving into the information values of immigrant and expatriate users of twitter. Issue 1 (27th December 2016) - Hyduk, Alyssa; Worrall, Adam
ABSTRACT: Information‐centric online communities are frequent sources for users who are seeking and sharing information, with greater sharing encouraged when users share similar judgments of information value. Information sharing and ICT use are especially important for immigrants and expats, but further research is needed into immigrants' use of ICTs and their information value judgments. This poster presents in‐progress research on how the ICTs used by expat and immigrant members of Twitter interact with the information values of community members. Findings show information value determination and negotiation are important for immigrants and expats online, with cultural, contextual, and economic values being most frequently invoked both explicitly and implicitly. A strong role for boundaries and some establishment of common ground was observed, but further exploration is necessary and planned of cases of information value negotiation, information sharing, and ICT use among this population to further our understanding of them in social, technical, and cultural contexts.